Evaluation of binding competition and group epitopes of acetylcholinesterase inhibitors by STD NMR, Tr-NOESY, DOSY and molecular docking: an old approach but new findings. Issue 10 (23rd September 2015) - Tanoli, Nazish U.; Tanoli, Sheraz A. K.; Ferreira, Antonio G.; Gul, Sana; Ul-Haq, Zaheer
Abstract : We suggest that the small inhibitors of AChE like coumarin and gallic acid's structure-based scaffolds may help in controlling Alzheimer's disease. Abstract : Acetylcholinesterase is an important enzyme, currently used as therapy for controlling the effects of Alzheimer's disease that has been accepted as one of the major threats to the elderly population. In this perspective, NMR-based binding studies were performed to probe the interligand binding competition and the inhibition potential aiming at a selected target. In the ligand recognition assay, the acetylcholinesterase–inhibitor complex was also validated through a site-specific inhibitor, gallic acid—a known competitive inhibitor. The STD competition experiments demonstrated that both inhibitors did not compete with gallic acid for the particular binding site. However, in competition STD experiments, the order of binding potential has also been calculated, which ranked gallic acid at the highest with 157 μM and 4-methylumbelliferone at the lowest with 165 μM K D value. Moreover, binding conformations and diffusion coefficients were calculated by using Tr-NOESY and DOSY, respectively. Finally, the dissociation constant ( K D ) information from DOSY was also calculated, which interestingly mimics exactly the pattern of the earlier STD-titration result. Following these NMR outcomes, docking simulations were applied and gallic acid was found as the second potent inhibitor with −5.0195 kcal mol −1 after 4-methylumbelliferone with a −5.4894 kcal mol −1 binding energy. From these realistic NMR results and theoretical docking approach, we envisioned that the utilized molecular scaffolds or their extensions might be used in the control of Alzheimer's disease. Moreover, these scaffolds could also be helpful in generating the rational design of some novel inhibitors with increased potency and even greater specificity.